Trends in Runoff From Dryland, Cropped Fields on the Texas High Plains, and Implications for Their Management - Baumhardt, R. Louis; Marek, Gary; Brauer, David (Frontiers in Sustainable Food Systems, 2020)
Capturing precipitation as soil moisture is essential for successful dryland crop production, especially in semi-arid regions. Runoff is a loss of precipitation that does not result in increased soil moisture. Therefore, understanding the factors affecting runoff from cropped fields is important to successful dryland farming. Runoff frequency and volume were assessed using data from 1990 to 2009 from a long-term wheat-sorghum-fallow rotation near Bushland, Texas (USA), an area with an annual precipitation of 500 mm and pan evaporation rate of over 2,000 mm. The likelihood that a rainfall event generated runoff increased with increasing rainfall volume such that all storms in excess of 50 mm yielded runoff. Runoff volume also increased with storm intensity. Rainfall in the preceding week was positively related to runoff volume. Runoff tended to be greater in no-till plots as compared to stubble mulched plots. During El Nino phase of the El Nino-Southern Oscillation the number of precipitations during the months of December through February tended to be higher. During La Nina phase of the El Nino-Southern Oscillation the number of precipitations during the months of November through January, respectively, tended to be lower. There also was a tendency for rainfall events during the El Nino phase to be of greater volume. However, the data did not support the hypothesis that greater winter rainfall with the El Nino event was associated with greater runoff. Therefore, greater rainfall during the El Nino phases should have been available for crop production. These results are discussed with regarding crop management practices for the Texas High Plains.